Increased Efficacy of Oral Fixed-Dose Combination of Amphotericin B and AHCC® Natural Adjuvant against Aspergillosis - Alba Pérez-Cantero; Dolores R. Serrano; Patricia Navarro-Rodríguez; Andreas G. Schätzlein; Ijeoma F. Uchegbu; Juan J. Torrado; Javier Capilla (MDPI AG, 2019)
Invasive pulmonary aspergillosis represents one of the most serious fungal infections among immunocompromised patients. In this study, we aimed to analyze the in vivo efficacy of prophylactic oral amphotericin B (AMB) encapsulated in modified chitosan-nanoparticles (Nanomerics’ Molecular Envelope Technology (MET)) supplemented with a standardized extract of cultured Lentinula edodes mycelia (AHCC®) in a murine model of pulmonary aspergillosis. We determined fungal burden and survival of mice and additionally, we carried out a cytokine analysis in an attempt to understand the immunomodulation of the extract. Our results evidenced equivalent efficacy between orally administered AMB-MET and the intravenous liposomal AMB marketed formulation. Addition of the AHCC® supplement significantly improved efficacy in terms of burden reduction and survival increase of both oral and intravenous AMB therapies compared to the untreated control group. Moreover, a protective effect of the extract was observed in terms of weight loss. Regarding the cytokine profiles, the Th1 immune response was stimulated in treated animals when compared to the control group. This response was marked by an enhancement in the MCP-1, GM-CSF, VEGF, RANTES and IL-17 levels and a decrease in the IL-6, a biomarker related to the severity of the infection.